Dual Function of Streptomyces sp. KKU215 in Biocontrol of Bacterial Wilt and Growth Promotion of Chili - Wongjiratthiti, Aroon; Sawiphak, Suwapha (Indochina Applied Sciences, 2026)
Bacterial wilt, caused by Ralstonia pseudosolanacearum, poses a serious threat to chili production. This study investigated the dual potential of Streptomyces sp. KKU215 as both a biocontrol agent against this pathogen and a plant growth-promoting bacterium for chili. The research involved in vitro antagonism assays, effects on chili seedling growth through seed priming, and effects in the biocontrol of bacterial wilt and growth promotion in pot experiments. In vitro assays confirmed that Streptomyces sp. KKU215 effectively inhibited R. pseudosolanacearum growth within 2 days, producing a clear zone with a diameter of 32.20 mm. Priming chili seeds with Streptomyces sp. KKU215 for 30 min significantly enhanced seedling growth 30 days after seeding, with increases in shoot length (14.21 vs. 12.25 cm), total length (21.05 vs. 18.63 cm), fresh weight (16.04 vs. 12.40 g), and dry weight (1.88 vs. 1.20 g), accompanied by a denser root system and larger leaves compared to the control. Most notably, in pot experiments, application of Streptomyces sp. KKU215 significantly suppressed bacterial wilt, achieving a disease severity reduction from 87.50% in the control to only 16.67% in the treated plants. Streptomyces sp. KKU215-treated seedlings showed enhanced growth, with enhanced growth, reaching maximum values for shoot length (28.26 cm), root length (24.93 cm), fresh weight (7.56 g), and dry weight (0.89 g). These findings highlight Streptomyces sp. KKU215 is a highly promising dual-function agent for sustainable chili cultivation. Further validation in field trials and the development of a stable formulation are essential next steps for practical application.